The source traditional medication knowledge: The dayak iban in lanjak deras village - Markus Iyus Supiandi; Leliavia Leliavia (STKIP Persada Khatulistiwa Sintang, 2020)
West Kalimantan consists of 151 sub-ethnics. One of them is the Iban found in Lanjak Deras Village, Batang Lupar District, Kapuas Hulu Regency, Indonesia. The Iban has such a long history regarding their insiht into traditional medicine to deal with health problems experienced by local people. However, their knowledge of traditional medication has not been well documented. Therefore, knowledge of traditional medication is considered very important to be documented as an effort to preserve cultural heritage. This study aimed to analyze the source of traditional medication knowledge in the Iban. The method used in this study was survey techniques. The data were obtained through semi-structured interviews. Descriptive qualitative was used to analyze the data. The result showed that the sources of the Ibans knowledge for traditional medication were derived from: family (100%), customary leader (100%), shaman (100%), experience (75%), experiment (75%), dreams (50%), verbally (100%), be informed (100%) and ask a question (100%). This shows that the dayak Iban tribe people get traditional medical knowledge from various sources.Keywords: Analysis, traditional medicine, plants medicine, dayak iban